The Influence of Anxiety Levels in Third Trimester Pregnant Women Through Health Education on Childbirth Preparation at the Marlina Clinic, Ciputat District, Tangerang Selatan City - Sari, Indah Permata; Puspitasari, Amalia Indah (Universitas Malahayati, 2025)
ABSTRACT The third trimester is an important period in pregnancy when the mother makes mental and physical preparations for childbirth. Untreated anxiety can increase the risk of complications during childbirth, such as premature labor and low birth weight babies. Additionally, anxiety is associated with the emergence of postpartum depression (PPD) and post-traumatic stress (PTS), which can result in a lack of emotional bonding with the baby. The aim of this study was to determine the influence of anxiety levels in third trimester pregnant women through health education on childbirth preparation at the Marlina Clinic, Ciputat District, Tangerang Selatan City, in 2024. This is a quantitative study using a quasi-experimental method. The research location is the Marlina Clinic, Ciputat District, Tangerang Selatan City. The research period starts from May 2024 until completion. The population in this study consists of pregnant women who received antenatal care from May to June 2024 at the Marlina Clinic, Ciputat District, Tangerang Selatan City. The sample in this research includes all third trimester primigravida pregnant women at the Marlina Clinic, totaling 30 people. The sampling technique used in this research is purposive sampling. The questionnaire used in this research was the Hamilton Anxiety Rating Scale (HARS). The bivariate analysis used in this research is the paired t-test. Based on the results of the frequency of respondent characteristics, most respondents were under 25 years old. The majority of respondents had a high school education, totaling 22 people. Respondents were predominantly mothers who did not work, totaling 21 people. Based on data on the frequency distribution of anxiety levels, the highest levels of anxiety before providing health education about childbirth preparation were moderate and severe anxiety. After providing health education about childbirth preparation, the level of anxiety was predominantly mild anxiety. Based on the table on the influence of anxiety levels, it can be seen that health education regarding childbirth preparation for third trimester pregnant women has a very significant effect on the anxiety levels of pregnant women. This is evident from the p-value of 0.00 < 0.05 (95% confidence level). Keywords: Anxiety, Pregnancy, Health Education, Antenatal Care, Third Trimester